Stroke in first‐degree relatives of patients with cervical artery dissection. (2nd April 2014) - Kloss, M.; Grond‐Ginsbach, C.; Pezzini, A.; Metso, T. M.; Metso, A. J.; Debette, S.; Leys, D.; Dallongeville, J.; Caso, V.; Thijs, V.; Bersano, A.; Touzé, E.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Patients with ischaemic stroke (IS) caused by a spontaneous cervical artery dissection (CeAD) worry about an increased risk for stroke in their families. The occurrence of stroke in relatives of patients with CeAD and in those with ischaemic stroke attributable to other (non‐CeAD) causes were compared. Methods The frequency of stroke in first‐degree relatives (family history of stroke, FHS) was studied in IS patients (CeAD patients and age‐ and sex‐matched non‐CeAD patients) from the Cervical Artery Dissection and Ischemic Stroke Patients (CADISP) database. FHS ≤ 50 and FHS > 50 were defined as having relatives who suffered stroke at the age of ≤50 or >50 years. FHS ≤ 50 and FHS > 50 were studied in CeAD and non‐CeAD IS patients and related to age, sex, number of siblings, hypertension, hypercholesterolemia, smoking and body mass index (BMI). Results In all, 1225 patients were analyzed. FHS ≤ 50 was less frequent in CeAD patients (15/598 = 2.5%) than in non‐CeAD IS patients (38/627 = 6.1%) (P = 0.003; odds ratio 0.40, 95% confidence interval 0.22–0.73), also after adjustment for age, sex and number of siblings (P = 0.005; odds ratio 0.42, 95% confidence interval 0.23–0.77). The frequency of FHS > 50 was similar in both study groups. Vascular risk factors did not differ between patients with positive or negative FHS ≤ 50. However, patients with FHS > 50 were more likely to have hypertension and higher BMI. Conclusion Relatives of CeAD patients had fewer strokes at a young age than relatives of non‐CeAD IS stroke patients.